Thyroid cancer histological subtypes based on tumor size: National perspective. Issue 9 (10th April 2020) - Al‐Qurayshi, Zaid; Foggia, Megan J.; Pagedar, Nitin; Lee, Grace S.; Tufano, Ralph; Kandil, Emad
Abstract: Background: Thyroid tumor size is an important prognostic factor. The aim of this study is to examine the histological subtypes and management of thyroid cancer based on tumor size (≤4 cm vs >4 cm). Methods: Retrospective cohort study utilizing the National Cancer Database, 2004‐2014. Results: A total of 152 387 patients were included, 13 614 (8.9%) of whom had a tumor size >4 cm. Histological subtypes of tumors >4 cm were: 69.6% papillary thyroid carcinoma, 17.5% FTC, 7.9% HCC, and 2.8% medullary thyroid carcinoma (MTC). High‐volume hospitals for thyroid surgery were less likely to perform two‐stage thyroidectomy, particularly for tumors ≤4 cm. Low‐volume hospitals had a higher risk of staged thyroidectomy for MTC ≤4 cm (19.8%) compared with high‐volume hospitals (8.7%) ( P < .001). Conclusions: This study describes the prevalence of thyroid cancer subtypes. In the era of a conservative approach to differentiated thyroid carcinoma, there could be a potential increase in the risk of staged thyroidectomy.